RESPON AL-QUR'AN PADA MASA JAHILIYAH DALAM KEADILAN SOSIAL DAN HAK ASASI MANUSIA - Nur Halisa S (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The period of Jahiliyah is known as a period of ignorance and social injustice that plagued Arab society before the advent of Islam, characterized by practices that degraded human dignity and violated human rights (HAM).The Qur'an comes as a revelation that provides a critical and solutive response to these conditions by upholding the principles of social justice and respect for human rights. This study aims to analyze how the Qur'an responds to social phenomena during the Jahiliyah period, especially in the context of social justice and human rights. The method used is the study of literature and textual interpretation of relevant verses of the Qur'an, as well as review of the concepts of jahiliyah and Islamic teachings related to human rights. The results of the study show that the Qur'an explicitly condemns the practices of jahiliyyah such as oppression, discrimination, and violation of the right to life, and affirms the principles of equality, justice, and respect for human dignity as fundamental values. It also teaches social responsibility and laws that protect the rights of individuals and groups. In conclusion, the Qur'an is not only a spiritual guide, but also the main source of social reform that rejects all forms of injustice and human rights violations that occurred during the Jahiliyah period, as well as an ethical and legal basis in building a just and civilized society.